Nebivolol Attenuates Neutrophil Lymphocyte Ratio: A Marker of Subclinical Inflammation in Hypertensive Patients - Mazhar Hussain; Muhammad Saeed; Muhammad Zafar Majeed Babar; Moazzam Ali Atif; Lubna Akhtar (International Journal of Hypertension)
Background. High value of neutrophil lymphocyte ratio (NLR) is a strong independent predictor and biomarker of ongoing vascular inflammation in various cardiovascular disorders. Objective. The main focus of the study is to investigate the effect of nebivolol on NLR in mild to moderate hypertensive patients in comparison with metoprolol. In addition, BMI, blood pressure, TLC count, blood sugar, and lipid profile were also assayed before and after treatment. Materials and Methods. In this 12-week prospective double-blinded randomized study, 120 patients with mild to moderate hypertension were randomly divided into two groups to prescribed daily dose of tab nebivolol 5–10 mg and metoprolol 50–100 mg, respectively, for 12 weeks. The data were analyzed using SPSS 16 software. Results. A total of 100 patients completed the study. Both drugs lowered blood pressure significantly, nebivolol 20.5/10.5 and metoprolol 22.5/11.2 (p<0.001) from baseline. Regarding inflammation, nebivolol reduced total leukocyte count (p=0.005) and neutrophil count (p=0.003) and increased lymphocyte count (p=0.004) as compared to metoprolol. Similarly, nebivolol but not metoprolol significantly reduced NLR ratio (p=0.07). Nebivolol improved lipid profile and blood sugar compared to metoprolol, but values were nonsignificant. Conclusion. Nebivolol has a strong impact on reducing NLR, a marker of subclinical inflammation in hypertensive patients. Moreover NLR can be used as a disease and drug monitoring tool in these patients.